1986
DOI: 10.3109/00365518609083684
|View full text |Cite
|
Sign up to set email alerts
|

High circulating levels of 25-hydroxyvitamin D3in renal stone formers with hyperabsorptive hypercalciuria

Abstract: Normocalcaemic male stone formers, 31-51 years old (n = 108) on a free diet, were divided into a hypercalciuric group (n = 47) with calcium excretion rates higher than 8.0 mmol/24 h, a normocalciuric group (n = 32) with calcium excretion rates below 6.1 mmol/24 h and an intermediate group (n = 29). There were no statistically significant differences between the hypercalciuric and the normocalciuric groups with respect to serum levels of calcium, phosphate, creatinine, urate, ALAT, albumin, PTH, 1,25-dihydroxyv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
2
15
1
Order By: Relevance
“…The increase of serum concentrations of 25(OH)D in InCHIANTI participants with high calcium excretion is likely to be explained by larger vitamin D store [31], and may be associated with increased renal 1.25(OH) 2 D synthesis [16,32]. This association may be observed in hypercalciuric stone formers, and has been attributed to an abnormal renal 25(OH)D hydroxylation activity [16,33].…”
Section: Discussionmentioning
confidence: 95%
“…The increase of serum concentrations of 25(OH)D in InCHIANTI participants with high calcium excretion is likely to be explained by larger vitamin D store [31], and may be associated with increased renal 1.25(OH) 2 D synthesis [16,32]. This association may be observed in hypercalciuric stone formers, and has been attributed to an abnormal renal 25(OH)D hydroxylation activity [16,33].…”
Section: Discussionmentioning
confidence: 95%
“…Large normal ranges of 25hydroxyvitamin D3 concentrations, their dependence on anti-rickets prophylaxis, seasonal variations and variable amounts of vitamin D3 in food products usually make impossible any interpretation of the results of random measurements of 25(OH)vitamin D3. High circulating levels of 25(OH)vitamin D3 in renal stone formers with hyperabsorptive hypercalciuria were reported [10]. Much more information is available on increased 1,25(OH)2vitamin D3 levels in variants of idiopathic hypercalciuria [9,11].…”
Section: Discussionmentioning
confidence: 97%
“…After full-text analysis, another 19 studies were excluded for the following reasons: 14 had no control group and no useful data, three did not provide standard deviations, and two reported duplicate data. Finally, 32 studies fulfilled our eligibility criteria and were enrolled in the meta-analysis [10,11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. …”
Section: Resultsmentioning
confidence: 99%
“…Most studies clearly demonstrated that they ruled out hyperparathyroidism and/or renal tubule acidosis [10,11,18,19,22,26,27,29,33,34,36,43], some also excluded patients using calcium and/or vitamin D [18,26,29,35,39,42]. Seventeen studies described their criteria of hypercalciuria and they were not consistent [18,19,20,22,24,26,28,29,32,35,36,37,38,42,43,45], twelve of which defined hypercalciuria as urinary calcium excretion of more than 300 mg/24 h for men and 250 mg for women or 4 mg/kg/day [19,23,26,28,29,32,35,36,38,42,43]. The subjects were on a free or normal calcium diet in some studies [10,11,19,21,22,26,28,29,32,35,36,39,43], while restricted calcium diets were adopted in some others [24,27,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation